(untitled) (Signifiances (Signifying), 2019)
This paper submits the peircian semiotic sign and the saussurean linguistic sign to the question of their phenomenogenesis : it explores the way in which the theoretical construction produces its resulting object under the guidance of prerequisites, methodologies and intentions. A comparative presentation of these two extreme approaches leads to the idea that the sign, both semiotic and linguistic, is to be envisages from a microgenetic viewpoint through its episodic and material occurrences, which are instrumental in constituting the human experience that emerges from actual practices which bring about the object. The study therefore relates with the enactive paradigm.